A Critical Discourse Analysis of School-Based Behavioural Policies: Reconceptualizing Understandings of Responses to Student (Mis)Behaviours - Colorado, Cara; Janzen, Melanie D. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
Students who have been labeled as having “behaviour problems” in the school system have some of the worst academic and social outcomes of any student group. In most Canadian provinces, responses to students who misbehave are legislated through Safe Schools policies intended to guide districts and individual schools in responding to student misbehaviour. In this research project, we conducted a critical discourse analysis of Manitoba’s Safe and Caring Schools documentation in order to analyze the ways in which provincial policies construct school-based responses to behaviours. Based on our analysis, recommendations for policy-makers to better support studentsinclude revising policies to reflect reconceptualized views of children, non-deficit understandings of behaviour, and ethical responses to student behaviour.